2017
DOI: 10.1186/s12989-016-0181-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle exposure reactivates latent herpesvirus and restores a signature of acute infection

Abstract: BackgroundInhalation of environmental (nano) particles (NP) as well as persistent herpesvirus-infection are potentially associated with chronic lung disease and as both are omnipresent in human society a coincidence of these two factors is highly likely. We hypothesized that NP-exposure of persistently herpesvirus-infected cells as a second hit might disrupt immune control of viral latency, provoke reactivation of latent virus and eventually lead to an inflammatory response and tissue damage.ResultsTo test thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 69 publications
(75 reference statements)
1
24
0
Order By: Relevance
“…A body of studies shows particle-induced induction of acute phase response in terms of increased Saa3 transcription and SAA3 release. [13,14,39,40,42,45,46,52,[91][92][93][94][95][96] Furthermore, Saa3 mRNA levels were increased within a few hours and SAA3 protein was measured by ELISA as early as 6 h after LPS instillation accumulating up to 24 h before slowly declining to base levels over a course of days. [97] (unpublished data) However, all these studies were conducted in bronchoalveolar lavage or whole lung tissue, and the responsible cell types have not yet been identified.…”
Section: Cells Expressing Acute Phase Response Proteins In the Lungmentioning
confidence: 99%
“…A body of studies shows particle-induced induction of acute phase response in terms of increased Saa3 transcription and SAA3 release. [13,14,39,40,42,45,46,52,[91][92][93][94][95][96] Furthermore, Saa3 mRNA levels were increased within a few hours and SAA3 protein was measured by ELISA as early as 6 h after LPS instillation accumulating up to 24 h before slowly declining to base levels over a course of days. [97] (unpublished data) However, all these studies were conducted in bronchoalveolar lavage or whole lung tissue, and the responsible cell types have not yet been identified.…”
Section: Cells Expressing Acute Phase Response Proteins In the Lungmentioning
confidence: 99%
“…In contrast to our study with TiO 2 ‐NP, nanocarbon black did not alter cell titers of herpes virus after a 2‐h primary infection (Sattler et al. 2017). However, nanocarbon black and double‐walled carbon nanotubes did increase viral titers in alveolar macrophages or mouse lungs with a latent rather than ongoing infection (Sattler et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, nanocarbon black and double‐walled carbon nanotubes did increase viral titers in alveolar macrophages or mouse lungs with a latent rather than ongoing infection (Sattler et al. 2017). Pulmonary exposure of mice to TiO 2 ‐NP 5 days prior to respiratory RSV infection increased the severity of RSV‐induced pneumonia, although lung viral titers were not significantly affected, perhaps due to the high level of viral inoculation used (Hashiguchi et al.…”
Section: Discussionmentioning
confidence: 99%
“…The noted increase in IAV titers could not be duplicated with a simultaneous dual exposure or by exposing the cells to the SWCNTs after infection (Sanpui et al 2014). However, in another study, DWCNTs were able to reactivate latent herpesvirus, suggesting that the infections occurred prior to NP exposure (Sattler et al 2017). There is not an abundance of evidence to suggest that classic additive, synergistic, or antagonistic toxicity occurs under any of these exposure scenarios, but this observation likely depends on the endpoints that are quantified, which have been limited.…”
Section: Nanoparticle and Viral Exposure Routes And Scenariosmentioning
confidence: 96%
“…Spherical carbon nanoparticles (Barras et al 2016) and fullerene (C60) derivatives (Shoji et al 2013) were shown to interfere with HSV-1 and IAV, respectively, whereas exposure to a single dose of TiO 2 nanoparticles exacerbated pneumonia in RSV-infected mice (Hashiguchi et al 2015a). Lastly, a more recent report showed for the first time the ability of double-walled carbon nanotubes (DWCNTs) to reactivate latent herpesvirus (MHV-68) in cells and mice (Sattler et al 2017). They also discovered that these DWCNTs could induce more pronounced effects in terms of reactivating latent virus than carbonaceous spherical nanoparticles.…”
Section: Nanoparticle Exposure and Viral Infectionmentioning
confidence: 99%